Novel compound heterozygous pathogenic variants in ASCC1 in a Chinese patient with spinal muscular atrophy with congenital bone fractures 2 : Evidence supporting a "Definitive" gene‐disease relationship - Weiliang Lu; Mingxing Liang; Jiasun Su; Jin Wang; Lingxiao Li; Shujie Zhang; Zailong Qin; Limei Huang; Yingchi Lu; Shang Yi; Sheng Yi; BoBo Xie; et al. (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background A very limited spectrum of ASCC1 pathogenic variants had been reported in six (mostly consanguineous) families with spinal muscular atrophy with congenital bone fractures 2 [OMIM #616867] since 2016. Methods A proband from a non‐consanguineous Chinese family presented with neonatal severe hypotonia, respiratory distress, muscle weakness, and atrophy, as well as congenital bone fractures was performed by exome sequencing. Results A compound heterozygosity of a nonsense (c.932C>G,p.Ser311Ter) and an exon 5 deletion in ASCC1 segregating with phenotypes was detected, both variants are novel and pathogenic. Since ASCC1 is a relatively new disease gene, we performed the gene curation by ClinGen SOP. The existing evidence is sufficient to support a "Definitive" level of disease‐gene relationship. Conclusion This case report expended the mutation spectrum of ASCC1 and support the notion that this novel disease also occurs in outbreed populations and this is a rare disease but may still be underdiagnosed due to its perinatal lethal outcomes.